Impact of Population Size and Aging on the Efficiency of Cancer Screening in Japanese Municipalities: Insights from Data Envelopment Analysis - Koshi Takahashi; Sho Nakamura; Yu Ogasawara; Masahiko Sakaguchi; Kaname Watanabe; Hiroto Narimatsu (Health Services Insights)
Background: Improving cancer screening participation is increasingly important. However, insufficient medical and financial resources have been reported to hinder program implementation; therefore, enhancing program efficiency is crucial. Although demographic factors have been reported to correlate with public health program efficiency, it remains unclear whether this applies to cancer screening. Objectives: To evaluate the efficiency of cancer screening programs conducted in Japanese municipalities and analyze their relationship with demographic characteristics, including population size and aging rates. Design: A cross-sectional study using national open-source data from 2019. Methods: We collected data from all 1741 Japanese municipalities in 2019 using a national open-source database. After applying inclusion criteria, 1593 municipalities were analyzed. Program efficiency was measured using Data Envelopment Analysis (DEA), with inputs including the number of public health nurses, medical institutions, and healthcare expenditure per target population. Outputs were cancer screening participation rates. Logistic regression was used to examine the relationships between efficiency, population size, aging rates, and their interaction. Results: Of the 1593 municipalities analyzed, 414 (26.0%) were deemed efficient. A statistically significant interaction between aging rates and population size was observed in the model predicting screening efficiency. In municipalities with aging rates above 31.4% (95% confidence interval [CI]: 29.2-37.1), larger target populations were associated with lower efficiency. Conversely, in municipalities with over 1075 screening targets (95% CI: 552-1381), higher aging rates were linked to lower efficiency. Conclusion: This study suggests that aging rates and population size may be associated with municipal-level differences in the efficiency of cancer screening programs. Understanding the mechanism underlying this relationship could help inform resource allocation and program design. Further research is warranted to explore these relationships more deeply and to support the development of more efficient screening strategies, particularly in the context of ongoing demographic shifts.